2000
DOI: 10.1039/b002267p
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of methyl hydrogen α-hydroxyiminobenzylphosphonates — kinetics, mechanism and the question of metaphosphate formation †

Abstract: The thermodynamics, pH dependency and solvent effects of the fragmentation reaction of a series of α-oxyiminobenzylphosphonate monomethyl esters [(E)-1a-f ] were examined in water and other hydroxylic solvents by UV and by 31 P NMR spectroscopy at pH 0-3.1. The fragmentation of compounds (E)-1a-f was found to be a first-order reaction in substrate over the acidity range studied, while the dependence on the acidity is more complex, with rate constants k 1 and k 2 . The ρ values corresponding to the first and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The central phosphoryl moiety is tending in structure toward a neutral phosphosphate ester, a species that has been implicated in the fragmentation of R-hydroiminophosphonates. 68 This again mirrors the behavior of phosphate monoester monoanions, and suggests a major role for intramolecular general acid catalysis using the phosphoryl OH. Both pathways have identical activation energies, suggesting that when there is a proton available for facile extraction by the departing leaving group, both stepwise and concerted pathways are equally viable.…”
Section: Discussionmentioning
confidence: 66%
“…The central phosphoryl moiety is tending in structure toward a neutral phosphosphate ester, a species that has been implicated in the fragmentation of R-hydroiminophosphonates. 68 This again mirrors the behavior of phosphate monoester monoanions, and suggests a major role for intramolecular general acid catalysis using the phosphoryl OH. Both pathways have identical activation energies, suggesting that when there is a proton available for facile extraction by the departing leaving group, both stepwise and concerted pathways are equally viable.…”
Section: Discussionmentioning
confidence: 66%
“…[1][2][3][4][5][6][7][8][9] Recently we published a detailed kinetic investigation of the fragmentation of methyl hydrogen α-hydroxyiminobenzylphosphonate ((E )-1) and some of its derivatives in water and in mixed alcohol-water solutions under acidic conditions. 10 The results were compatible with a dissociative mechanism (D N *A N or D N ϩ A N ). The thermodynamics, and especially the different solvent effects on the fragmentation rate, on the one hand, and on the products on the other, indicated that the rate limiting step and the product determining step do not share a common transition state, and that the reaction coordinate includes at least one reactive intermediate, probably methyl metaphosphate (Scheme 1).…”
Section: Introductionmentioning
confidence: 56%
“…However, we should expect equilibrium formation of the ketone, PhCOPO(OH)OMe. Assuming that k 4 and k Ϫ4 are similar for (E )-1 and (E )-2 and using Dynafit 18 we can calculate that in the concentration range used for NMR analysis in the case of (E )-1 (around 0.04 M), 10 we should expect to see a maximum of 0.0048 M (12%) of the ketone after 70 min but only an easily unnoticeable 0.002 M (5%) after 5 hours when the reaction was actually checked.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the thermodynamics, pH dependency and solvent effects of this fragmentation reaction was studied on a series of para-substituted -oxyiminobenzylphosphonate monomethyl esters, 38, in water and other hydroxylic solvents [21]. Briefly, the fragmentation reaction requires acidic conditions and there was practically no fragmentation observed above pH 3.…”
Section: Methyl Estermentioning
confidence: 99%
“…As an anion, the oxime OH needs not to be considered as a leaving group. The full mechanistic scheme for the hydronium catalyzed and uncatalyzed fragmentation, involving pre-equilibrium formation of the reactive forms, which proceed to products, is described in paper [21]. The only significant sources of fragmentation are the protonated oxime (cation) and the The observed solvent isotope effects, k H /k D ~ 0.6, indicate that the reaction proceeds via specific acid catalysis and that fragmentation of the neutral species is in accord with a pre-equilibrium proton transfer in the ground state.…”
Section: Methyl Estermentioning
confidence: 99%